Description of critical behaviour of model systems using non-Gaussian measures (Yukhnovskii's approach) - Kozlovskii, M.P.; Patsahan, O.V. (Condensed Matter Physics, 2000)
We present a brief review of the works devoted to a study of critical phenomena in three-dimensional model systems dwelling on the Yukhnovskii approach in detail. This approach which is based on the use of non-Gaussian measures allows one to obtain both universal and non-universal quantities. In order to illustrate the advantages of the approach proposed by I.R.Yukhnovskii we apply it to a study of non-universal quantities, namely: (1) the phase transition temperature of a 3D one-component lattice model, (2) the gas-liquid critical point properties of ﬂuid systems.